Cómo usar el cerebro en las aulas : para mejorar la calidad y acelerar el aprendizaje - Garnett, Steve, 1966- (Educación hoy (Narcea (Firm)), 2014)
A realistic, practical and accessible book that allows teachers to incorporate the best of recent brain-based research into teaching.